Resource Optimization of D2D-Assisted CR Network With NOMA for 5G and Beyond Systems - Waqas, Muhammad; Ejaz, Waleed; Sidhu, Guftaar A. S.; Aslam, Saleem (IEEE internet of things journal, 2022)
Device-to-device (D2D) communication has emerged as a potential candidate for 5G and beyond networks to optimize spectrum utilization, reduce power consumption, and support higher data rates. The energy and spectral efficiency of D2D communication can be enhanced further by adapting cognitive radio (CR), nonorthogonal multiple access (NOMA), and radio-frequency energy harvesting (RF-EH) technologies. Therefore, this article proposes a sum-rate maximization problem for a D2D-assisted CR network with NOMA, considering the RF-EH mechanism. A joint optimization problem is modeled to maximize the sum throughput of cellular and D2D nodes by considering power assignments, radio resource allocation, user pairing, and transmission time ratio assignment. The problem is then converted into a standard convex optimization problem subject to power allocations at individual nodes, interference temperature limits, individual data rate, and secrecy capacity. The duality theory is adopted to decompose the problem into multiple subproblems, and Karush-Kuhn-Tucker (KKT) conditions are applied to provide the solution. Finally, the proposed schemes are validated through simulation results. The proposed schemes outperform the existing schemes in terms of sum throughput and energy harvesting under different quality of service requirements.